Methods for Detecting the Environmental Coccoid Form of Helicobacter pylori - Mazaheri Assadi, Mahnaz; Chamanrokh, Parastoo; Whitehouse, Chris A.; Huq, Anwar (Frontiers in Public Health, 2015)
Helicobacter pylori is recognized as the most common pathogen to cause gastritis, peptic and duodenal ulcers, and gastric cancer. The organisms are found in two forms: 1) spiral-shaped bacillus and 2) coccoid. H. pylori coccoid form, generally found in the environment, is the transformed form of the normal spiral-shaped bacillus after exposed to water or adverse environmental conditions such as exposure to sub-inhibitory concentrations of antimicrobial agents. The putative infectious capability and the viability of H. pylori under environmental conditions are controversial. This disagreement is partially due to the fact of lack in detecting the coccoid form of H. pylori in the environment. Accurate and effective detection methods of H. pylori will lead to rapid treatment and disinfection, and less human health damages and reduction in health care costs. In this review, we provide a brief introduction to H. pylori environmental coccoid forms, their transmission and detection methods. We further discuss the use of these detection methods including their accuracy and efficiency.